Pengembangan Media Pembelajaran berupa Video Tutorial Materi Sulaman Burci - Suliyanthini, Dewi; Latifatuzzahroh, Latifatuzzahroh; Noerharyono, M. (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study aims to develop media video tutorials on burci embroidery materials to improvelearning outcomes and student learning effectiveness. The method used in this study is the R&Dmethod with the PPE (Planing, Production, Evaluation) model. The object of this research is aburci embroidery tutorial video development product. The subjects of this study were students ofclass XI Fashion Design at SMK Negeri 3 Cikarang Barat, with students XI A Fashion Design as asmall group trial of 12 students, and students XI B Fashion Design as a large group trial of 38students. The results of this study indicate that tutorial videos on burci embroidery material canimprove learning outcomes and student learning effectiveness. The burci embroidery tutorial videoobtained very decent criteria with a score of 95% for assessment by material experts and 83.3%for media experts. The burci embroidery tutorial video has proven to be effective in learning withthe average score of students in the small group trials for the pre-test and for the post-testincreasing to 85.17. The average score in the large group trials for the pre-test was 75.71 and forthe post-test it increased to 85.13 with an average increase of 9.42. Overall, it can be concludedthat the burci embroidery tutorial video media has proven to be very appropriate and effective tobe used as a teaching aid in the subject of making fashion ornaments.